MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA DENGAN MENGGUNAKAN MODEL PEMEBELAJARAN REALISTIC MATHEMATICS EDUCATION DI KELAS V SD KARTIKA 1-2 MEDAN - Nelli Arjuna Simarmata; Asnita Hasibuan; Ester J. Simarmata; Darinda Sofia Tanjung (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
This article discusses the students’ mathematics learning outcomes by using the Realistic Mathematics Education learning model for the fifth-grade students of SD Kartika 1-2 Medan and describes the obstacles faced by using the Realistic Mathematics Education learning model to improve students’ mathematics learning outcomes. The results indicated that there was an improvement of the fifth-grade students’ learning outcomes on Mathematics learning subjects at SD Kartika 1-2 Medan. It was proven from the research outcomes conducted on the pretest, students who achieved a maximum score were 5 students or 21.73%, while students who did not complete were 18 students or 78.27%. After the research was continued in the first cycle, students who achieved a complete score were 14 students or 60.86%, while students who did not complete were 9 students or 39.14%. Related to this, there was an improvement in the first cycle compared to the pre-test. Nevertheless, it did not qualify predetermined completeness category. Hence, it was continued to the second cycle, students who achieved a complete score were 20 students or 86.95%, while students who did not complete were 3 students or 13.05%. Thus, there was an improvement in cycle II compared to cycle I and had qualified the predetermined completeness. In addition, the teachers’ activities in the first cycle of observation achieved an average of 60%, and in the second cycle, it increased to 78%. Meanwhile, students’ activities in the learning process achieved 58%, and in the second cycle, it increased to 84%.